Improvement of the potency of microalgae Nannochloropsis and Chaetoceros through antioxidant analysis and optimization of DNA isolation. Issue 1 (July 2021) - Zulkarnain, M I; Rahayu, H T; Herida, A P; Erfianti, T; Kusumaningrum, H P; Zainuri, M; Endrawati, H; Widowati, I; Haryanti, W D U; Mahendrajaya, R T
Abstract: Nannochloropsis and Chaetocero s are microalgae that commonly used as natural feed for aquaculture animals. These microalgae are able to produce secondary metabolites that is used as an antioxidant. The objective of the study was to analyze the antioxidant activity from both microalgae using the DPPH method in relation with their DNA quality and quantity. The method for DNA isolation optimation was Doyle and Doyle method with slight modification. The results of this research showed the percentage of inhibition of Nannochloropsis and Chaetocero s were 9.72 % and 5.78%, respectively. While optimization of DNA isolation exhibited that Nannochloropsis was 193, 5 ng/ul with a purity of 1, 99 while Chaetoceros was 93.9 ng / µl with a purity of 2.00.